2018
DOI: 10.1016/j.appet.2018.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Brain response to food cues varying in portion size is associated with individual differences in the portion size effect in children

Abstract: Large portions promote intake of energy dense foods (i.e., the portion size effect--PSE), but the neurobiological drivers of this effect are not known. We tested the association between blood oxygen level dependent (BOLD) brain response to food images varied by portion size (PS) and energy density (ED) and children's intake at test-meals of high- and low-ED foods served at varying portions. Children (N = 47; age 7-10 years) participated in a within-subjects, crossover study consisting of 4 meals of increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 79 publications
0
19
2
1
Order By: Relevance
“…However, the lack of a significant change in the trajectory of energy intake when accounting for non-study foods demonstrates the robust effect of portion size on young children's intake. The mechanisms underlying the effect of portion size in children are not clear (38), but may be related to the activation in brain regions associated with reward (39) or the perception that it is appropriate to eat more food when larger portions are served (40). The finding that larger portion sizes led children to eat substantially more than their energy requirements over 5 d indicates that oversized portions can overwhelm a child's regulatory system and that further investigation is needed to identify modifiable mechanisms underlying this effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of a significant change in the trajectory of energy intake when accounting for non-study foods demonstrates the robust effect of portion size on young children's intake. The mechanisms underlying the effect of portion size in children are not clear (38), but may be related to the activation in brain regions associated with reward (39) or the perception that it is appropriate to eat more food when larger portions are served (40). The finding that larger portion sizes led children to eat substantially more than their energy requirements over 5 d indicates that oversized portions can overwhelm a child's regulatory system and that further investigation is needed to identify modifiable mechanisms underlying this effect.…”
Section: Discussionmentioning
confidence: 99%
“…One potential contribution to differences in eating behavior between male and female children is variation in neural processing of food cues. Food cues elicit responses in brain regions implicated in executive function, subjective valuation (e.g., orbitofrontal cortex), and visual processing (e.g., fusiform gyrus) [106] that are correlated with eating behaviors [107,108]. Several studies have observed sex differences in neural response to food cues.…”
Section: Biopsychosocial Contributions To Sex Differencesmentioning
confidence: 99%
“…Food cues elicit responses in brain regions and viewed through a mirror mounted on the head coil using a magnet-compatible projector. The protocol for task design and image development has been reported elsewhere 107,115 . In brief, children analyses were then conducted using energy density contrasts (high-ED -low-ED) derived from parameter estimates for each portion size condition separately, as well as a composite (i.e., across both portion sizes).…”
Section: Neural Differences In the Response To Food Cuesmentioning
confidence: 99%
“…21 implicated in executive function, subjective valuation (e.g., orbitofrontal cortex), and visual processing (e.g., fusiform gyrus)105 that are correlated with eating behaviors106,107 . Several studies have observed sex differences in neural response to food cues.…”
mentioning
confidence: 99%